HUBUNGAN KECERDASAN EMOSIONAL IBU DENGAN PERKEMBANGAN ANAK USIA 1-3 TAHUN DI PUSKESMAS BALAM MEDAN - Simorangkir, Lindawati; Barus, Mardiati; Stefani Natalis Ndruru (JURNAL KEPERAWATAN, 2024)
Background: Development is the increasing ability of a child where in this case toddlers need special needs. Objective: The purpose of this study is to determine the relationship between Mother's Emotional Intelligence and the Development of Children Aged 1-3 Years at Balam Health Center Medan. Method: This type of research is quantitative with a cross-sectional research design. Population are 60 respondents. The sampling technique uses total sampling. The instrument used is a questionnaire. Result:  show that the mother's emotional intelligence was good (46.7%), the mother's emotional intelligence is sufficient (53.3%) and the criteria for normal in children (91.7%) and the criteria for suspect in children (8.3%). Data analysis used univariate and bivariate with the Spearman rank test. Conclusion: The Spearman rank statistical test (rho) obtained the value of r = (-.282) and p value = 0.029 (p <0.05) which means that there is a significant relationship between Mother's Emotional Intelligence and the Development of Children Aged 1-3 Years at Balam Health Center Medan. It is hoped that mothers will understand emotional intelligence better in all existing factors. Keywords: Relationship; Mother's emotional intelligence; Child Development